123k views
1 vote
Hi May I know how to balance this

Hi May I know how to balance this-example-1

1 Answer

1 vote

Answer:

2Ba₃(PO₄)₂ +6SiO₂ ⇒ P₄O₁₀ +6BaSiO₃

Step-by-step explanation:

Equating coefficients, you get ...

aBa₃(PO₄)₂ +bSiO₂ ⇒ cP₄O₁₀ +dBaSiO₃

For Ba: 3a = d

For P: 2a = 4c

For O: 8a +2b = 10c +3d

For Si: b = d

__

Expressing everything in terms of b and c, we get ...

d = b

a = b/3 = 2c

From the second, b = 6c, so we have ...

a = 2c

b = 6c

c = c

d = 6c

And we can write the equation with c=1 as ...

2Ba₃(PO₄)₂ +6SiO₂ ⇒ P₄O₁₀ +6BaSiO₃

User Malka
by
5.9k points